Visual Representation of the Process of Scientific Production in the Field of Value Co-creation in Fintech Startups - Behzadnia, Mehrdad; Nayebzadeh, Shahnaz; Hataminasab, Seyyed Hassan; Dehghani Ashkezari, Mohammad Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Fintech startups have revolutionized consumer behavior by introducing innovative business models. The concept of value co-creation has emerged as a collaborative effort involving companies, suppliers, employees, and customers. This article aims to examine the scientific production trend in the field of value co-creation within fintech startups from 1997 to 2023.Methodology: The research was carried out using the interpretive paradigm and a systematic review approach, employing specific search terms in the Scopus database to analyze 122 articles (utilizing VOS viewer 1.6.19 software). The application of scientometrics in the marketing field represents a fresh approach that highlights the intellectual paradigm guiding the co-creation of value in international managerial research.Findings: A thorough examination of the articles revealed that the majority of research conducted on the topic was centered in the United States. The findings from the research analysis indicated that various aspects including entrepreneurship, innovation, investment, financial services, and stakeholders have been extensively studied in relation to value co-creation in fintech startups.Conclusion: The research on fintech startups is currently in its early stages of development. This study represents a groundbreaking endeavor to examine the existing literature on value co-creation and establish a framework that focuses on enhancing marketing performance.